SANITARY AND HYGIENIC WATER PURIFICATION RESEARCH FOR THE WATER SUPPLY CLOSED SYSTEM OF THE FLYING APPARATS - N. A. Salnikov; N. E. Nikolaykina (Научный вестник МГТУ ГА, 2016)
The approved technological schemes and technical means for the water purification, which is formed at implementation of sanitary and hygienic procedures onboard the operated space stations are considered and compared. Data of various sources on a chemical composition of water pollution after different types of the works performed by crew before sanitary procedures are provided. The choice of the washing antibacterial means, the technological scheme of cleaning locates. The scheme of experimental installation for purification of sanitary and hygienic water with method of the return osmosis and the made experiments results is provided.It is shown, that it is essentially possible to carry out regeneration of sanitary and hygienic water with the help of the reverse-osmosis modules released by the industry. Selectivity of the reverse-osmosis modules of various production to the chosen detergent exceeds 99%, and at pressure difference on a membrane of 0,8–10 MPa the pure extraction coefficient of 98% is reached. Express methods for a preliminary estimate of oxygen chemical consumption and detergent concentration in the polluted water, a method of an assessment of water purification quality on specific conductivity are offered.